Calotropin and corotoxigenin 3-O-glucopyranoside from the desert milkweed Asclepias subulata inhibit the Na+/K+-ATPase activity - Meneses-Sagrero, Salvador E.; Rascón-Valenzuela, Luisa A.; García-Ramos, Juan C.; Vilegas, Wagner [UNESP]; Arvizu-Flores, Aldo A.; Sotelo-Mundo, Rogerio R.; Robles-Zepeda, Ramon E. (PeerJ, 2022)
Na+/K+-ATPase is an essential transmembrane enzyme found in all mammalian cells with critical functions for cell ion homeostasis. The inhibition of this enzyme by several cardiotonic steroids (CTS) has been associated with the cytotoxic effect on cancer cell lines of phytochemicals such as ouabain and digitoxin. This study evaluated the inhibitory capacity of cardenolides calotropin and corotoxigenin 3-O-glucopyranoside (C3OG) from Asclepias subulata over the Na+/K+-ATPase activity in vitro and silico. The inhibitory assays showed that calotropin and C3OG decreased the Na+/K+-ATPase activity with IC50 values of 0.27 and 0.87 mM, respectively. Furthermore, the molecules presented an uncompetitive inhibition on Na+/K+-ATPase activity, with Ki values of 0.2 mM to calotropin and 0.5 mM to C3OG. Furthermore, the molecular modeling indicated that calotropin and C3OG might interact with the Thr797 and Gln111 residues, considered essential to the interaction with the Na+/K+-ATPase. Besides, these cardenolides can interact with amino acid residues such as Phe783, Leu125, and Ala323, to establish hydrophobic interactions on the binding site. Considering the results, these provide novel evidence about the mechanism of action of cardenolides from A. subulata, proposing that C3OG is a novel cardenolide that deserves further consideration for in vitro cellular antiproliferative assays and in vivo studies as an anticancer molecule.
Keywords: Asclepias subulata; ATPase activity; Cardenolides; Uncompetitive inhibition